SIX CULTURE HOFSTEDE AND STUDENT ACADEMIC FRAUD AT PRIVATE UNIVERSITIES IN BALI - I Gusti Ayu Ratih Permata Dewi (International Journal of Social Science, 2024)
Academic fraudulent behavior is a dishonest act that violates ethics in the academic sphere at both the student, lecturer and administration levels which harms other parties. This research wants to test the influence of Hofstede's cultural dimensions on student academic fraud. This research was conducted at Warmadewa University in Bali. The population in this study were 2020 Even semester students of the Accounting Department, Faculty of Economics and Business, Warmadewa University in Bali, totaling 2456 students. To determine the minimum sample size, the researcher used the Slovin formula, namely 100 students as a sample. This research uses an interval scale with 5 Likert scales. Data analysis in research uses Partial Least Square (PLS) with the SmartPLS program. The results show that the cultural dimension of power distance has no effect on academic fraud, the cultural dimension of uncertainty avoidance has a negative and significant effect on academic fraud, the cultural dimension of individualism has a negative and significant effect on academic fraud, the cultural dimension of masculinity has a positive and significant effect on academic fraud, the cultural dimension of orientation long term has a negative and significant effect on academic fraud, and the cultural dimension of indulgence has a negative and significant effect on academic fraud